PENGARUH PENGELOLAAN AIR DAN BAHAN ORGANIK TERHADAP PRODUKTIVITAS AIR DAN POTENSI HASIL PADI (Oryza sativa L.) - Bagus Yulianto; Florentina Kusmiyati; Ali Pramono (BUANA SAINS, 2020)
The aim of this research was to evaluate the effect of water management and organic matter on water productivity and rice yield potential. The study was conducted at the Indonesian Agricultural Environment Research Institute located on Jl. Raya Jakenan - Jaken Km 05 Pati, Central Java from December 4, 2019 to March 27, 2020. The research was carried out using a factorial completely randomized design of 2 x 2 with 4 replications. The first factor was water management (continuous flooding (CF) as high as 5 cm and Alternate Wetting Drying (AWD). The second factor was organic matter (cow manure 3 tons/ha, and without organic matter). The results showed that the treatment of water management and organic matter produced a number of tillers, 1000 grain weight, and yield potential were not significantly different. Water management of alternate wetting  drying and organic matter of 3 tons/ha was able to produce higher average dry grain yields and consumed less water so that the value of water productivity  was higher than the treatment of continuous flooding water management